Workshop Penggunaan Teknologi Digital sebagai Media Pembelajaran di SDN 3 Rejo Binangun - Eny Maulita Purnama Sari; Ahmad Efendi; Ariyani Etik Kurniasari Kurniasari; Neli Novita Sari; Ashifah Rahma Dewi (Pakis Journal Institute, 2026)
The rapid advancement of digital technology requires teachers to develop competencies in utilizing various educational applications to enhance the quality of teaching and learning processes. However, many teachers have not yet optimally integrated digital technologies into English language instruction and student creativity development. The Community Service Program aimed to improve teachers’ knowledge and skills in utilizing Duolingo as a platform for English language learning and Canva as a tool for fostering student creativity, supported by the use of a smart board. The program was implemented through workshops, demonstrations, hands-on training, and mentoring sessions. The participant are 11 teachers and 18 students. The program effectiveness was evaluated using pre-tests, post-tests, observations, and questionnaires. The results indicated a significant improvement in teachers’ knowledge, increasing from 27.27% in the pre-test to 81.82% in the post-test. Teachers’ skills in using Duolingo and Canva also improved substantially, rising from 36.36% to 100%. Furthermore, all participating teachers demonstrated a strong interest in integrating digital technology into their teaching practices and expressed a willingness to collaborate in developing technology-based learning media. Participant satisfaction reached 90%, indicating that the program successfully addressed the needs of both teachers and students. Overall, the program contributed to strengthening teachers’ digital competencies and promoting more interactive, engaging, and creative learning environments.